The franchine model as positioning strategy of SMEs in restuarant- bar sector in Sinaloa - Morales Avila, Myrna Cristina (2017)
This research was conducted in the city of Culiacán, Sinaloa, during the period from 2015 to 2016, taking as an object of study small and medium enterprises (SMEs) Whirl restaurant- bar and comparing the business model used by entrepreneursin the same industry with franchise models, that is, to solve the problem to which this business is facing in terms of operational faults which already handle their short stay in the market in which they develop.